P78 Impact of severe allergic asthma in children: highlighting a role for understanding the family perspective. (16th November 2010) - Staley, K G; Herzallah, R; Pandya, H; Humphreys, E; Gaillard, E
Abstract : Introduction and objectives: Current understanding of paediatric severe allergic asthma tends to focus on the impact of the disease on the child in isolation from the impact on the wider family. We aimed to characterise a paediatric severe asthma population and assess the practical, financial and emotional burden on the family. Methods: Case-note review of children (6–18 years) with severe, allergic asthma (BTS treatment step 4–5) was performed; identifying treatments, disease characteristics and practical limitations (e.g. missed schooldays, impingement on activities). Interviews with the primary care-giver of a child with severe allergic asthma were conducted and aimed to explore the impact of severe asthma on the overall family (e.g. missed workdays, time dedicated to care). Family profiles and cost-modelling will be performed to assess the emotional and economic impact on families of having a child with severe allergic asthma. Results: 35 children from a severe asthma clinic between 2007 and 2010 were identified. Despite being on maximum or near-maximum treatment, nearly 50% of children reported symptoms that impacted on daily activities, or were troublesome at night. Furthermore, 40% reported poor school attendance due to asthma symptoms. When performed, the Asthma UK Asthma Control Test identified a mean score of 15 (range 10–25); with 5/6 patients reporting a score below 20 (very poor control). Data also suggests that the unpredictable nature of severe asthma has an impact on the child and family unit. For example, it was documented how a child felt 'constantly…frightened of these episodes of shortness of breath'. Parents used the words 'catastrophic' and described how they were simply 'fed-up with poor asthma control', highlighting the perceived impact and frustration at caring for a child with severe asthma. Further work on family profiles and cost-modelling is being undertaken to assess the emotional and economic impact on a family of having a child with severe asthma. Conclusion: These preliminary findings suggest that caring for a child with severe asthma has a considerable impact on the functioning of the family unit. A better understanding of the family perspective on the impact of severe allergic asthma in children may help improve outcomes by enabling the development of specific strategies.